Linguistic authority, language ideology, and metaphor : the Czech orthography wars - Bermel, Neil (Language, power, and social process ;, 2007)
How does a country find itself 'at war' over spelling? This book focuses on a crucial juncture in the post-communist history of the Czech Republic, when an orthographic commission with a moderate reformist agenda found itself the focus of enormous public.